2017
DOI: 10.1167/iovs.17-22581
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal Thickness In and Outside of Vascular Arcade in Healthy Eyes Using Spectral-Domain Optical Coherence Tomography

Abstract: The CT generally decreased with age, but it decreased much faster in old age than in relatively younger people. CT displayed large variations among different points in and outside of the vascular arcade. The thickest choroid was located at the point superior to the fovea, not the fovea itself. Such physiological variations should be considered when interpreting pathologic changes of the choroid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 28 publications
2
11
1
Order By: Relevance
“…e mean ChT measured in our study was between the thickest temporal and the thinnest nasal values in consensus with previously published studies [15]. However, according to Ikuno et al [22] and Park et al [31], the central point showed the thickest ChT in the adult population. Furthermore, ChT exhibited significant variation across the posterior pole in healthy children, with it being thicker in the central regions [25].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…e mean ChT measured in our study was between the thickest temporal and the thinnest nasal values in consensus with previously published studies [15]. However, according to Ikuno et al [22] and Park et al [31], the central point showed the thickest ChT in the adult population. Furthermore, ChT exhibited significant variation across the posterior pole in healthy children, with it being thicker in the central regions [25].…”
Section: Discussionsupporting
confidence: 92%
“…Multiple studies reported a ChT of 251-341 μm in children with a mean SER of ±0.05 D, and 309.57-354 μm in healthy adults of different races [22,25,26,[29][30][31]. However, the ChT of myopic children aged 10-15 years was reported to be 303 μm [16,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this series of healthy subjects ages 25 to 55 years with ALs in the normal range, we found a mean subfoveal CT of 340 ± 99 µm, which is within the limits of recent publications that used SS-OCT and found that the subfoveal CT varied from 229 to 379 µm. 13 , 20 , 26 , 27 , 38 , 39 , 47 51 The significant variation in subfoveal CT values could be explained by differences in patient demographics (mainly the age range 13 , 14 , 16 , 45 and the refractive error or AL 5 , 45 , 52 ) and the way in which CT was measured (subfoveal or within the central 1-mm diameter, swept-source or EDI SD-OCT). In our series, the subfoveal CT was >395 µm in 30% of cases, a significant proportion which has not been highlighted before.…”
Section: Discussionmentioning
confidence: 99%
“…The thickness of the choroid varies regionally across the macular and peripheral regions . Further, structural changes in the choroid across a wide field may contribute to the pathophysiology of a range of ocular conditions including myopia, age‐related macular degeneration, central serous chorioretinopathy and glaucoma .…”
mentioning
confidence: 99%